Synthesis and assessment of properties of ZrB2 nanopowder utilizing boro/carbothermal reduction method - Omid khanali; Mehri Mashhadi; Alireza Salim Pour; Farhad Farhang Rad (International Journal of Ceramic Engineering & Science, 2023)
Abstract The reason of this study is to synthesize ZrB2 nano powder utilizing boric acid and phenolic resin. Within the study of zirconia as a source of zirconium, boric acid was used as a source of boron and phenolic resin as a carbon source. The theoretical and experimental studies of ZrB2 were synthesized by boro/carbothermal diminishment from the novel sol–gel technology. The zirconia powder was crushed for 8 h and in conjunction with different molar proportions of boric acid, in this consider, a kinetic demonstrate for reactions creating ZrB2 was built up based on thermodynamic analysis. The resultant powder was synthesized in a neutral atmosphere controlled in 1450°C and 1550°C. After it was also observed that, with the increase of molar proportion of H3BO3, the reaction delivered ZrB2 powders in high amount of the boron reaction. The compound was analyzed by an X‐ray diffraction technique and found to be ZrB2 powder that was synthesized with the purity of approximately 98%.